Colorectal cancer in ulcerative colitis: a cohort study of primary referrals from three centres. Issue 2 (February 1988) - Gyde, S N; Prior, P; Allan, R N; Stevens, A; Jewell, D P; Truelove, S C; Lofberg, R; Brostrom, O; Hellers, G
Abstract : A retrospective cohort of 823 patients with ulcerative colitis who resided at the time of diagnosis in one of three defined geographical areas (West Midlands region, Oxford region, England and Stockholm County, Sweden) was assembled. The patients were first seen at named hospitals in these areas and the diagnosis of ulcerative colitis established within five years of onset of symptoms between 1945-1965. All patients were 15 years of age or more at onset of disease and were followed for a minimum of 17 years and a maximum of 38 years. Ninety seven per cent completeness of follow up was achieved. Examining the colorectal cancer risk in the series relative to the risk in the general population by standardised morbidity ratios, there was an eight fold increased risk of cancer in the series as a whole. Dividing the series by extent of colitis, extensive colitis patients showed a 19 fold increase in risk. A four fold increased risk was shown in the remainder of the series (left sided colitis, proctitis and extent unknown). Life table analyses in extensive colitis gave cumulative risks of 7.2% (CI 3.6-10.8) at 20 years from onset of disease and 16.5% (CI 9.0-24.0) at 30 years from onset. No significant effect of age at onset, sex or referral centre could be detected. Examination of the data by interval from onset to cancer and by actual age at development of cancer suggests that patients who develop colorectal cancer will do so in a distribution around 50 years of age independent of duration of disease in adult onset ulcerative colitis (greater than 15 years at onset of disease). An inverse relationship was shown between age at onset of disease and interval from onset of disease to cancer. Further age specific rates for cancer increased up to 50 years and decreased thereafter. These results suggest that extensive colitis patients have a genetic predisposition to colorectal cancer and that longstanding inflammation is not of primary importance in the initiation/promotion of cancer in this disease.